Survei Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Muay Thai SMAN 1 Tongas - Hadi Sutejo; Afifan Yulfadinata (MAN Insan Cendekia Jambi, 2026)
In order to promote students' capacity to engage in physical activities at their best, particularly in extracurricular sports, physical fitness is crucial. This study uses the Indonesian Student Fitness Test (TKSI) to assess the physical fitness of Muay Thai extracurricular students at SMAN 1 Tongas. Twenty male students served as the subjects of this quantitative descriptive research. The study instruments included T-tests, beep tests, depping tests, hand-eye coordination tests, vertical jump tests, and hand-touch reaction tests. The data was analyzed using descriptive statistics in Microsoft Excel. The findings indicated that the majority of the components of arm muscular endurance, leg muscle explosive power, eye and hand coordination, and response speed fell into the good to very good range. In the meanwhile, the intermediate group dominated the cardiorespiratory endurance and agility components. Students who participated in Muay Thai extracurricular activities often had a moderate to high level of physical condition. These results show that Muay Thai extracurricular activities enhance students' physical fitness, but more organized training is still required to increase cardiorespiratory endurance and agility.